A Pythagorean tree fractal shape stub-loaded resonator as a UWB bandpass filter with wide stopband. Issue 5 (26th June 2021) - Kumari, Puja; Sarkar, Pankaj; Ghatak, Rowdra
Abstract: A compact ultrawideband (UWB) bandpass filter (BPF) is designed by harnessing the efficacy of a Pythagorean tree fractal shape stub-loaded resonator. The design inherently provides the passband transmission poles, which make it convenient to be used in wide passband filtering circuits. The number and the position of the resonating modes can be controlled by increasing the iterations of the Pythagorean tree, as analyzed using odd- and even-mode analysis. Design steps of the BPF are detailed. The designed UWB BPF takes up a small circuit area of (12.13 × 9.59) mm 2 . The proposed design is fabricated and measured to verify the simulated results. The stopband is extended up to 17.5 GHz with a maximum attenuation of 15 dB.